Research status and hot topics of the effects of skin innervation on wound healing from 1959 to 2022: A bibliometric analysis - Song, Ru; Wu, Zhenjie; Ma, Jiaxu; Yin, Siyuan; Liu, Chunyan; Sun, Rui; Cao, Guoqi; Lu, Yongpan; Chen, Aoyu; Zhang, Guang; Liu, Jian; Wang, Yibing (Frontiers in Surgery, 2022)
Background: Skin innervation plays an important role in wound healing by either direct contact with or indirect secretions that impact skin cells. Many studies in this field have been published; however, there is a lack of bibliometric analyses focusing on the effect of skin innervation on skin wound healing. In this study, we aimed to analyse the research trends, status and hotspots in this field. Methods: Reviews and articles published in English were extracted from the Web of Science Core Collection (WoSCC) database based on subject term searches. Microsoft Office Excel, VOSviewer and CiteSpace were used to analyse publication date, country or region, institution, author and author keywords. Results: A total of 368 papers published between 1959 and 2022 were included in the analysis. Although there was a pulsation during this period, there was an overall upwards trend in studies related to the effect of skin innervation on wound healing. The USA, particularly the University of Washington, and Gibran, Nicole S. from the University of Washington, was the most active in this field. Wound Repair and Regeneration published the most relevant literature, and “Calcitonin gene-related peptide: physiology and pathophysiology” had the highest total number of citations. “Diabetic foot ulcer”, “epidermal stem cells”, “mesenchymal stem cells” and “mast cells” are current and potential future research hotspots. Conclusion: This bibliometric analysis will inform on the overall trends in research related to the effect of skin innervation on wound healing, summarize relevant research hotspots and guide future work.